An ultra-rare case of immunoskeletal dysplasia with neurodevelopmental abnormalities in an Indian patient with homozygous c.953C > T variant in EXTL3 gene: a case report - Shruti Bajaj; Purnima Satoskar; Aadhira Nair; Frenny Sheth; Jayesh Sheth; Harsh Sheth (BMC, 2022)
Abstract Background Immunoskeletal dysplasia with neurodevelopmental abnormalities (ISDNA) is an ultra-rare genetic condition that belongs to the group of spondyloepimetaphyseal dysplasias. It is caused due to presence of biallelic variants in the EXTL3 gene. The encoded exostosin like glycosyltransferase 3 (EXTL3) protein plays a key role in heparan sulfate synthesis. The skeletal and nervous systems are prominently affected in ISDNA with variability in immunological manifestations. Here, we report the 15th case of ISDNA (third patient of an Indian ancestry) in the world, along with a review of literature. Case presentation A 15-month-old female child with clinical indications of global developmental delay, short stature, coarse facial features, and hypotonia was referred to our clinic. Spondyloepimetaphyseal dysplasias associated with extra-skeletal manifestations was suspected based on clinic-radiological correlation. Whole exome sequencing analysis revealed the presence of a homozygous known pathogenic variant c.953C > T (p. Pro318Leu) in exon 3 of the EXTL3 gene, thereby confirming diagnosis of ISDNA. Conclusion We present an ultra-rare case of ISDNA- third patient of Indian ancestry and only the 15th reported case in the literature. On review of all cases in the literature, we find that the affected individuals show abnormalities primarily in three systems namely- skeletal, nervous and immune system. Notably, patients harbouring the same variant in EXTL3 gene show phenotypic variability especially with respect to presence or absence of immunological manifestations, suggesting a role of unknown modifiers. Hence, it is currently not possible to correlate the variant position in the EXTL3 gene with disease severity.